# Difference between revisions of "Power of a Point Theorem/Introductory Problem 2"

m (proofreading) |
Wwilliamtang (talk | contribs) m (→Solution) |
||

Line 5: | Line 5: | ||

== Solution == | == Solution == | ||

− | Applying the Power of a Point Theorem gives <math> 6\cdot x = 4\cdot 1 </math>, | + | Applying the Power of a Point Theorem gives <math> 6\cdot x = 4\cdot 1 </math>, so <math> x = \frac 23 </math> |

''Back to the [[Power of a Point Theorem]].'' | ''Back to the [[Power of a Point Theorem]].'' |

## Latest revision as of 13:14, 16 July 2017

## Problem

Find the value of in the following diagram.

## Solution

Applying the Power of a Point Theorem gives , so

*Back to the Power of a Point Theorem.*